Exclusive initial-state-radiation production of the DD̄, D*D̄, and D*D̄* systems - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Lopez, L; Palano, A; Pappagallo, M; et al. (2009)
We perform a study of the exclusive production of DD̄, D*D̄, and D*D̄* in initial-state-radiation events, from e+e- annihilations at a center-of-mass energy near 10.58.